The role of ecdysone in the timely development of the Drosophila melanogaster brain - Oliveira, Andreia Costa (2018)
Tese de mestrado, Biologia Evolutiva e do Desenvolvimento, Universidade de Lisboa, Faculdade de Ciências, 2017